Teacher's Experiences of Using Digital Storytelling in Early Childhood Education in Indonesia: A Phenomenological Study - Purnama, Sigit (Jurnal Pendidikan Islam, 2021)
Digital storytelling is an important component of early childhood education (ECE) because it can help capture and expand their imagination. The purpose of this study was to explain early childhood teachers' beliefs about the use of digital storytelling in their classrooms. This research was conducted in Yogyakarta, Indonesia. Phenomenological methods are used to understand and describe these phenomena and the essence of ECE teachers' experiences. The results showed that the experience of ECE teachers in learning using digital storytelling in the classroom had many benefits in improving the quality of learning. This study provides guidelines for ECE teachers on how technology can be integrated into children's learning activities using digital storytelling. The results of this study can also contribute to teachers to better understand the impact of using such technology to improve the development of technological literacy in early childhood education.